Insights into the nature of technology diffusion and implementation the perspective of sociotechnical alignment - Molina,. Alfonso H.
This paper is about the diffusion or implementation of technology in the design process of a microprocessor company. It aims at casting further light on the nature of the processes whereby technologies eventually gain company recognition over (or along with) others. It focuses on the influence of social behavioural factors in the outcome of this process as well as on the role played by the nature of the 'incoming' technology and its relation to the company design process. More broadly, it seeks to advance the systematic treatment of these aspects into a unified understanding of intra-company technology diffusion or implementation. The argument details with the issues through a combination of theoretical analysis and the case study of the British microprocessor company Inmos. It conducts a targeted review of concepts relevant to the nature of implementation, leading to the empirical analysis of a new technology (i.e., formal methods) born in a university environment and later transferred into the design process of Inmos. The discussion uses the author's sociotechnical constituencies approach and treats the industrial diffusion of formal methods as a process of constituency building at an intra-organisational level. Especially relevant to this analysis is the process of sociotechnical alignment underpinning constituency building. The main issues raised by the intra-organisational experience of 'formal methods' are discussed.
By means of theoretical analysis and a case study of a microprocessor company the author suggests a method for unifying the diffusion of technology and social behavioural factors.